Pengaruh Terapi Akupunktur dan Elektroakupunktur terhadap Penurunan Skala Nyeri Pinggang - Sholichan Badri; Sumanto Sumanto; Jatmiko Rinto Wahyudi (Jurnal Terapi Wicara dan Bahasa, 2026)
Background: Low back pain is a common disorder involving the muscles, nerves, and bones of the back. Acupuncture has been widely used as a method to treat low back pain. Objectives: This study aims to determine the effect of acupuncture and electroacupuncture therapy on reducing low back pain. Methods: A quasi-experimental design with a two group pre test-post test design approach was used, involving 30 subjects experiencing low back pain. Subjects were divided into two groups: a treatment group that received electroacupuncture intervention and a control group that received manual acupuncture intervention. The intervention was performed 4 times at a frequency of twice a week for 2 weeks. Pain levels were measured using the QVAS scale before and after the intervention. Results: The analysis showed a significant reduction in the group that received the intervention, and electroacupuncture intervention had a greater effect on the pain scale for low back pain compared to the control group. Conclusion: Electroacupuncture has been proven to be more effective in reducing low back pain. Keywords: Electroacupuncture, Manual acupuncture, Low back pain